2003
DOI: 10.1093/jn/133.7.2302
|View full text |Cite
|
Sign up to set email alerts
|

Fat and Protein from Olive Oil-Fried Sardines Interact to Normalize Serum Lipoproteins and Reduce Liver Lipids in Hypercholesterolemic Rats

Abstract: Fatty fish consumption has been recommended due to its high (n-3) PUFA content. However, an effect of its protein on serum lipids and lipoproteins has also been suggested. The present study was designed to determine the acceptability of diets containing sardines fried in olive oil or the fat extracted from those sardines and the normalization of serum lipids and lipoproteins, the hepatic lipid profile, and the fatty acid composition of the liver of growing Wistar rats fed these diets after dietary loading of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
21
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 32 publications
13
21
0
Order By: Relevance
“…In accordance with previous results [4] , after 2 weeks of cholesterol withdrawal total TC levels decreased signifi cantly. Despite the low n-3 PUFA content of the S diet ( table 2 ), TC levels decreased to within the normal rat range in these S animals [14] .…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In accordance with previous results [4] , after 2 weeks of cholesterol withdrawal total TC levels decreased signifi cantly. Despite the low n-3 PUFA content of the S diet ( table 2 ), TC levels decreased to within the normal rat range in these S animals [14] .…”
Section: Resultssupporting
confidence: 92%
“…The information on the effect that the consumption of fried-oily fi sh has on serum cholesterol is scarce. In previous studies, we observed that olive oilfried sardines produced a powerful hypocholesterolemic effect in hypercholesterolemic rats [3,4] .…”
mentioning
confidence: 91%
“…Boron trifluoride/ methanol was used for fatty acid methyl ester (FAME) preparation [22]. A Shimadzu gas chromatograph (Model GC-2014, Kyoto, Japan) fitted with a capillary column SP TM -2330 (60 m 0 0.25 mm  0.2 mm id) (Supelco, Inc, Bellefonte, USA) was used with a flame ionisation detector (FID).…”
Section: Fatty Acid Profilementioning
confidence: 99%
“…Boron trifluoride/ methanol was used for fatty acid methyl ester (FAME) preparation (Sánchez-Muniz, García Linares, García Arias, Bastida, & Viejo, 2003). A Shimadzu gas chromatograph (Model GC-2014, Kyoto, Japan) fitted with a capillary column SP™-2330 (60 m × 0.25 mm × 0.2 μm i.d.)…”
Section: Fatty Acid Profilementioning
confidence: 99%